An assessment of the environmental impact of cargo transport by road and sea in Iceland - Gernez, Etienne (2011)
The environmental impact of cargo transport is qualiﬁed and quantiﬁed in the Westfjords and Nothern regions of Iceland. A simpliﬁed Life Cycle Assessment (LCA) framework is applied to 5 transport scenarios: 1 land-based scenario reﬂecting the existing oﬀer in Iceland and 4 maritime alternatives (2 sailing routes, 2 types of ships). Using a statistical energy consumption model and up-to-date emission factor databases, the results show that the best maritime alternative is the one calling at the harbours of Reykjavík, Ísafjördur and Akureyri, using a Roll On-Roll Oﬀ (Ro-Ro) ship. Compared to land-based transport, the Ro-Ro alternative has a lower impact in most categories except those related to NOx and SOx emissions. With monetisation methods used for the internalisation of external costs, we show that a modal shift from land to sea comes as an overall beneﬁt to the Icelandic society. A Net Present Value (NPV) analysis is suggested to improve the economic calculations, as well as a context-based calculation of the value of time. Further possible improvements are advised in the emission inventory and characterisation phases. A ﬁnal recommendation is issued for future transport policy in Iceland. VAXVEST